Influence of production on the presence of patulin and ochratoxin A in fruit juices and wines of Argentina - Oteiza, Juan Martín (2017)
In this study, the relative frequency and concentration of patulin (PAT) and ochratoxin A (OTA) in fruit juices and wines collected in Argentina between 2005 and 2013 were determined by high performance liquid chromatography. PAT was detected in 1997 of 5958 samples (ranging from 3.0 to 19,622 μg/L), and 510 samples presented PAT levels above 50 μg/L. The highest incidence of PAT was observed in 2005 (243 of 419 samples) while the lowest was quantified in 2009 (104 of 482 samples). OTA was detected in only 22 of 1401 samples at concentrations ranging from 0.15 to 3.6 μg/L, and the highest incidence was observed in 2007 (8 of 153 samples). The concentration of PAT and OTA in the beverages analyzed was found to be affected by the type of fruit product, fruit commodity and production year. A great amount of data on the incidence of these mycotoxins in these matrixes can be further used in the development and reinforcement of measures to reduce the burden of their presence in juices and wines. This is important since PAT levels above the limit set by regulations were high and fruit juices are quite consumed by children. Although OTA contamination was low, effective ways to safeguard consumer exposure to PAT and OTA and consequently to protect public health are essential and indispensable.